1991
DOI: 10.1111/j.1471-4159.1991.tb08181.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Rate of Expression and Biosynthesis of Neuropeptide Y After Kainic Acid‐Induced Seizures

Abstract: Recent studies have shown marked increases in brain content of neuropeptide Y (NPY) after seizures induced by intraperitoneal injection of kainic acid and after pentylenetetrazole kindling in the rat. We have now investigated possible changes in the rate of biosynthesis of NPY after kainic acid treatment, by using pulse-labeling of the peptide and by determining prepro-NPY mRNA concentrations. For pulse labeling experiments, [3H]tyrosine was injected into the frontal cortex, and the incorporation of the amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…NPY expression was found markedly increased in hilar GABAergic interneurons, granule cells and sprouted mossy fibers (Bellmann et al, 1991;Chafetz et al, 1995;Lurton and Cavalheiro, 1997;Scharfman et al, 1999Scharfman et al, , 2002Sperk et al, 1992;Takahashi et al, 2000;Vezzani et al, 1996). NPY in the dentate gyrus can influence synaptic transmission and neurogenesis, demonstrates remarkable plasticity after seizures (Scharfman and Gray, 2006), and may have an anticonvulsive action (Furtinger et al, 2001;Klapstein and Colmers, 1997;Vezzani et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…NPY expression was found markedly increased in hilar GABAergic interneurons, granule cells and sprouted mossy fibers (Bellmann et al, 1991;Chafetz et al, 1995;Lurton and Cavalheiro, 1997;Scharfman et al, 1999Scharfman et al, , 2002Sperk et al, 1992;Takahashi et al, 2000;Vezzani et al, 1996). NPY in the dentate gyrus can influence synaptic transmission and neurogenesis, demonstrates remarkable plasticity after seizures (Scharfman and Gray, 2006), and may have an anticonvulsive action (Furtinger et al, 2001;Klapstein and Colmers, 1997;Vezzani et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that a major part of transduced prepro-NPY is processed in a conventional way through the regulated secretory pathway into synaptic vesicles by prohormone convertases (Bellmann et al, 1991;Day et al, 1992). Expression of prohormone convertases is indeed upregulated in the brain after kainic acidinduced seizures (Marcinkiewicz et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the antianxiety action of both these compounds is in line with the above-mentioned concept about the role of Glu transmission in anxiety. On the other hand, studies of the interdependence of glutamate and NPY in the hippocampus have shown that glutamatergic activation increases the synthesis and expression of NPY in hippocampal neurons (Schwarzer and Sperk, 1998;Schwarzer et al, 1996;Marksteiner et al, 1990;Bellmann et al, 1991;Bendotti et al, 1991) and that NPY inhibits Glu transmission in this structure (Silva et al, 2005;Tu et al, 2005; Klapstein and Colmers, 1997; Bijak and Śmiałowska, 1995; Figure 6 Photomicrographs showing NPYmRNA expression in emulsion-covered coronal sections from the region of dentate gyrus (DG) of the rat hippocampal formation. An increase in a number of labelled neurons and in grain density over individual neurons is seen after L-SOP (b) and L-CCG-I (c) microinjection in comparison with the control (a).…”
Section: Anxiolytic Effect Of Intrahippocampal Mglur Ligands and Npy mentioning
confidence: 99%
“…It contains numerous NPY interneurons and is rich in mGluRs (Kohler et al, 1986;Redrobe et al, 1999;Dumont et al, 1998). It was revealed that the enhancement of glutamatergic transmission strongly stimulated NPY synthesis and/or increased the content of that peptide in the hippocampus Bellmann et al, 1991;Schwarzer et al, 1996). Thus, it seemed of interest to find out whether anxiolytically active mGluR ligands could regulate NPY neurons in the hippocampal formation and whether such an interaction was engaged in their antianxiety effects.…”
Section: Introductionmentioning
confidence: 99%